Phosphorylation of histone H4 Ser1 regulates sporulation in yeast and is conserved in fly and mouse spermatogenesis. - Krishnamoorthy, T.; Chen, X.; Govin, J.; Cheung, W.L.; Dorsey, J.; Schindler, K.; Winter, E.; Allis, C.D.; Guacci, V.; Khochbin, S.; Fuller, M.T.; Berger, S.L. (Genes & Development, 2006)
Sporulation in Saccharomyces cerevisiae is a highly regulated process wherein a diploid cell gives rise to four haploid gametes. In this study we show that histone H4 Ser1 is phosphorylated (H4 S1ph) during sporulation, starting from mid-sporulation and persisting to germination, and is temporally distinct from earlier meiosis-linked H3 S10ph involved in chromosome condensation. A histone H4 S1A substitution mutant forms aberrant spores and has reduced sporulation efficiency. Deletion of sporulation-specific yeast Sps1, a member of the Ste20 family of kinases, nearly abolishes the sporulation-associated H4 S1ph modification. H4 S1ph may promote chromatin compaction, since deletion of SPS1 increases accessibility to antibody immunoprecipitation; furthermore, either deletion of Sps1 or an H4 S1A substitution results in increased DNA volume in nuclei within spores. We find H4 S1ph present during Drosophila melanogaster and mouse spermatogenesis, and similar to yeast, this modification extends late into sperm differentiation relative to H3 S10ph. Thus, H4 S1ph may be an evolutionarily ancient histone modification to mark the genome for gamete-associated packaging.